Sistem Pakar Diagnosa Kerusakan Hardware Komputer Mengunakan Metode Case Based Reasoning - Masdin, Asrafiah; Abduh, Hisma; Paembonan, Solmin (Lembaga Pengembangan Kinerja Dosen, 2024)
The purpose of this study is to design and create an Expert System for Diagnosing Hardware Damage on Computers Using the Case Based Reasoning Method. This expert system is created so that computer users can know the initial picture of what damage is happening to their computer hardware. The application created is designed using Unified Modelling Language (UML) which consists of usecase diagrams, activity diagrams, sequence diagrams, and class diagrams. The software used in the design of this application uses PHP programming language, XAMPP as webserver, MySql as database. This research produces an expert system application for diagnosing computer hardware damage using the case-based reasoning method which consists of several data management features that can only be done by admins. This app has been tested using accuracy testing methods. With this application, it is expected to help computer users find out the types of damage that are vulnerable to computer hardware and solutions to overcome the damage.